Strategic Dimension of Municipal Real Estate Stock Administration - Trojanek, Maria (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The aim of the paper was to prove the legitimacy of the strategic approach to administration of municipal real estates. The author introduced the legal and economic aspects of the municipal real estate stock administration, and she emphasized the specificity and goals set in the process of administrating the subject stock. In the course of the research, the arguments for reshaping the municipal real estate stock administration model were identified. The arguments were based on the assumption that the administration process should be derived from the classification of real estates according to (current and future) municipal tasks and needs stipulated in strategic documents. The study also comprised the description of activities taken up by local authorities in subsequent stages of designing the strategy of municipal real estate administration.